(untitled) (Journal of Hama University, 2022)
Disinfection of hatching eggs with disinfectants, is an important and essential way to reduce the bacterial contamination on the surface of the eggshell. The formaldehyde fumigation method has been used for many years to disinfect hatching eggs. Due to the toxicity of formaldehyde and its carcinogenic effect of the hatchery workers, it was necessary to find other methods for disinfecting the hatching eggs. Therefore, this study was conducted by using hydrogen peroxide 3% as a spray at different times, and formaldehyde as evaporation, in four frequency trials, to disinfect hatching eggs of broiler breeders. A number of 2,400 eggs of Ross 308 breed, collected from clean egg nests from commercial broiler breeder flock in Hama governorate, at the age of 30 - 33 weeks (Peak production period), every week 600 eggs from a different house. 240 samples (10%) were taken, 60 samples from every frequency from the surface of eggshells by using a cotton swab with nutrient broth, and the bacterial count was performed in the laboratory after the disinfection of eggs by the methods specified by the experiment. The results showed that the values of the total bacterial count of eggs disinfected by using hydrogen peroxide 3% by spraying at the different times used in the experiment, were less and better than the results of the total bacterial count on the surface of the eggshell using fumigation with formaldehyde. The using of hydrogen peroxide 3% one-time spraying after 24 hours of collecting and preserving eggs, and using hydrogen peroxide 3% two times, the first after collecting the eggs and the second after 24 hours of preserving the eggs, are the best in reducing total bacterial count on the surface of eggshell.